Family farms as an instrument of agricultural development in the Europian Union and the challenge of transforming the agrarian structure in Ukraine - Suchoń, Aneta (My University, 2023)
In the world, agricultural activity is often carried out as part of a family farm. Such a farm is often run by the family with the help of third parties (especially during harvest). These kind of farm can be small, medium or larger units. The United Nations declared in 2014 the International Year of Family Farming, with the primary objective of supporting, developing and strengthening all types of family farming. Family farms play an important role in achieving the objectives of the EUʼs common agricultural policy. It is a valuable sustainable model in social, economic terms and environmental matters. Under art. 23 the Polish Constitution, the basis of the agricultural system of the state is the family farm. The definition is included in the Act of 11 April 2003 on shaping the agricultural system.